2008
DOI: 10.1111/j.1742-4658.2008.06538.x
|View full text |Cite
|
Sign up to set email alerts
|

The product chain length determination mechanism of type II geranylgeranyl diphosphate synthase requires subunit interaction

Abstract: The product chain length determination mechanism of type II geranylgeranyl diphosphate synthase from the bacterium, Pantoea ananatis, was studied. In most types of short‐chain (all‐E) prenyl diphosphate synthases, bulky amino acids at the fourth and/or fifth positions upstream from the first aspartate‐rich motif play a primary role in the product determination mechanism. However, type II geranylgeranyl diphosphate synthase lacks such bulky amino acids at these positions. The second position upstream from the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Based on structure and sequence comparisons with plant GGPPSs, the two-chamber architecture of LSU in the Mp GPPS structure provides additional cavities (CP hole and EC) for accommodating the longer product of C 20 -GGPP ( Figure 5; see Supplemental Figure 12 online). Our proposed two-chamber mechanism in which the product chain length is regulated by intersubunit interaction is distinct from the previous single-chamber molecular ruler mechanism for wellstudied homomeric PTSs, which use bulky residues to serve as flooring at the bottom of each enzyme active site to block further product chain elongation (Ohnuma et al, 1996;Tarshis et al, 1996;Hemmi et al, 2003;Guo et al, 2004aGuo et al, , 2004bSun et al, 2005;Chang et al, 2006;Noike et al, 2008). When the elongation barrier is removed in the active site of these enzymes by substituting the bulky residue with a smaller one, longer chain length products are generated.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Based on structure and sequence comparisons with plant GGPPSs, the two-chamber architecture of LSU in the Mp GPPS structure provides additional cavities (CP hole and EC) for accommodating the longer product of C 20 -GGPP ( Figure 5; see Supplemental Figure 12 online). Our proposed two-chamber mechanism in which the product chain length is regulated by intersubunit interaction is distinct from the previous single-chamber molecular ruler mechanism for wellstudied homomeric PTSs, which use bulky residues to serve as flooring at the bottom of each enzyme active site to block further product chain elongation (Ohnuma et al, 1996;Tarshis et al, 1996;Hemmi et al, 2003;Guo et al, 2004aGuo et al, , 2004bSun et al, 2005;Chang et al, 2006;Noike et al, 2008). When the elongation barrier is removed in the active site of these enzymes by substituting the bulky residue with a smaller one, longer chain length products are generated.…”
Section: Discussionmentioning
confidence: 76%
“…The function and structure of homomeric PTSs, such as FPPS and GGPPS, have been well studied (Ohnuma et al, 1996;Tarshis et al, 1996;Hemmi et al, 2003;Hosfield et al, 2004;Chang et al, 2006;Gabelli et al, 2006;Kavanagh et al, 2006aKavanagh et al, , 2006bKloer et al, 2006;Rondeau et al, 2006;Guo et al, 2007;Noike et al, 2008). The sequences of different enzymes generally contain <30% conserved amino acids (see Supplemental Figure 1 online).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutational and crystallographic analyses of homodimeric type II GGPPs (C 20 synthesis) from Pantoea ananatis and from Sinapis alba (SaGGPPs) (PDB code 2J1P), respectively, have suggested that the bottoms of the clefts were located at the subunit interface (15,34) (Fig. 5C).…”
Section: Overall Structure Of Ml-hexpps and Structural Comparison-mentioning
confidence: 99%
“…On the other hand, the interior part of the cleft accommodates the hydrophobic tail of the reaction product. The size of the cleft is strongly involved in the regulation of the final product chain length (9,11,12,26,(33)(34)(35)(36)(37)(38)(39). The crystal structure of GGPP synthase from Saccharomyces cerevisiae (Sc-GGPPs) with its final product GGPP revealed that the hydrophobic tail of the product just fits the cleft in both of the two homodimeric subunits (18).…”
mentioning
confidence: 99%